Petrography and geochemistry of exported colombian coals: Implications from correlation and regression analyses (2021)
The petrology of coal, as determined by the microscopic analysis of organic and inorganic elemental constituents of coal, provides information on its nature and characteristics. Coal is used worldwide in the production of thermal energy and coke. In the case of high-quality Colombian coals, only limited studies have been carried out. The present study presents the geochemical, mineralogical, and petrological characteristics of coal samples collected from Puerto Drummond in Cienaga, Colombia, to predict their potential uses. Therefore, the ultimate, proximate, petrographic, gross calorific value (GCV), ash fusion temperature, Fourier transform infrared spectroscopy (FTIR), X-ray diffraction (XRD), X-ray fluorescence (XRF), and Thermogravimetric (TG) analyses were employed in this study. The petrological analysis reveals that Colombian coals are naturally more abundant in vitrinite (72%) than inertinite (14–23%) macerals. Silicates and aluminosilicate are the main minerals present as fine particles mixed with macerals. The XRD and FTIR analyses show that the most common and dominant minerals are quartz, while gypsum, hematite, calcite and mica occur in lesser amounts. The oxide composition of the coal ashes consists of 51–58% SiO2 and 18–25% Al2O3 as determined by XRF analysis. In correlation and regression analysis, the moisture content shows a reverse correlation with GCV (Regression value of R2 = 0.68). This study helps researchers to comprehend the importance of Colombian coals and presents various techniques for characterisation of coals.